Feeding difficulties in children with cerebral palsy - Hikari Ambara Sjakti; Damayanti Rusli Syarif; Luh Karunia Wahyuni; lmral Chair (Indonesian Pediatric Society, 2008)
Background Children with cerebral palsy (CP) often have feedingdifficulties due to their disability. This results in inadequate calorieintake which finally leads to malnutrition. Several studies foundthat 30-90% of children with CP have feeding difficulties associ-ated with malnutrition. There has been no sufficient publisheddata about this problem in Indonesia.Objective To determine the prevalence of feeding difficulties andmalnutrition in children with CP.Methods A cross-sectional study was done from January toSeptember 2005 in the pediatric outpatient clinic of Dr. CiptoMangunkusumo Hospital (CMH). Children with CP underwentnutritional and feeding difficulties assessment. Nutritional sta-tus was determined by the ratio of body weight to body heightstandardized to CDC-NCHS 2000 growth curve and wereclassified based on Waterlow. Calorie intake was evaluated bydietary analysis and defined as adequate if it reached 13.9 kcal/em BH Â± 10%. Feeding difficulties assessment included historytaking, physical examination and observation of feeding skill inthe outpatient clinic.Results Fifty-five children with CP were included in this study,most of them were spastic type, mainly spastic diplegic and spasticquadriplegic cerebral palsy (SQCP). Malnutrition was found in76% subjects, most were SQCP. Feeding difficulties were found in76% subjects, half of them were SQCP, 38% with spastic diplegic.Thirty- eight percents of the parents whose children had feedingdifficulties was not aware of these problems in their children.Parallel with data above, 78% subjects received inadequatecalorie intake.Conclusions The prevalence of undernourished and severemalnutrition in children with CP is 66% and 11% respectively.Malnutrition in CP patients tends to be related with inad-equate calorie intake due to feeding difficulties that is found in78% subjects especially those with SQCP